2015
DOI: 10.3389/fncel.2015.00064
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 in the brain—connections with aging-associated disorders and lifespan

Abstract: The silent mating type information regulation 2 proteins (sirtuins) 1 of class III histone deacetylases (HDACs) have been associated with health span and longevity. SIRT1, the best studied member of the mammalian sirtuins, has a myriad of roles in multiple tissues and organs. However, a significant part of SIRT1’s role that impinges on aging and lifespan may lie in its activities in the central nervous system (CNS) neurons. Systemically, SIRT1 influences energy metabolism and circadian rhythm through its activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
113
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(120 citation statements)
references
References 169 publications
(208 reference statements)
3
113
0
4
Order By: Relevance
“…7). SIRT1 is an energy-sensing molecule that regulates PGC-1α, a transcriptional co-activator playing critical roles in regulating cellular energy metabolism (Ng et al 2015) and myelin formation (Rafalski et al 2013). SIRT1 protein was elevated by 1.2-fold by the combined effects of high fat consumption and exercise (P = 0.006), but not by either intervention alone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7). SIRT1 is an energy-sensing molecule that regulates PGC-1α, a transcriptional co-activator playing critical roles in regulating cellular energy metabolism (Ng et al 2015) and myelin formation (Rafalski et al 2013). SIRT1 protein was elevated by 1.2-fold by the combined effects of high fat consumption and exercise (P = 0.006), but not by either intervention alone.…”
Section: Resultsmentioning
confidence: 99%
“…SIRTs have emerged as key metabolic sensors that directly link environmental signals to metabolic homeostasis and stress responses. SIRT1 is a histone/protein deacetylase that regulates the activity of a variety of transcription factors and co-regulators, including PGC-1α to increase mitochondrial function, energy metabolism and gluconeogenesis (Ng et al 2015). Increases in spinal cord PLP and MBP protein under the influence of high dietary fat in combination with exercise occurred in conjunction with increases in SIRT1, suggesting a possible link between the events that warrants further study.…”
Section: Discussionmentioning
confidence: 99%
“…Together, our findings illustrate a neuroprotective mechanism whereby RPC via neuronal Sirt1 promotes glycolytic efficiency to combat energetic stress. These results have far-reaching implications, as dysregulation of glycolysis plays a role in the pathogenesis and/or manifestation of Huntingtin’s disease, Alzheimer’s disease and Parkinson’s disease, in all of which Sirt1 has a neuroprotective role 40, 41 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it is generally accepted that a higher activity of sirtuins is associated with protection against the majority of age-related diseases such as type 2 diabetes, cardiovascular disease, and Alzheimer's disease. [15][16][17][18] Notably, a calorie restriction diet (CR), the only intervention known so far to extend healthspan and lifespan, leads to SIRT1 and SIRT3 overexpression. 19,20 It has been also shown that SIRT1 transgenic mice present features similar to those of animals fed a CR: they are lean, resistant to cancer, as well as to the diet-induced metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%